(untitled) (Marketing Journal, 2025)
This article provides a comprehensive overview of the formation of business models in the context of the digital economy and the role of information and communication technologies (ICT) in this process. It outlines the sources and founders of traditional a nd digital business models, as well as analyzes the differences between them. The activities of widely implemented digital platforms were also discussed.